Cover Image, Volume 27, Issue 5. Issue 5 (May 2017) - Haidar, M.; Guèvremont, G.; Zhang, C.; Bathgate, R.A.D.; Timofeeva, E.; Smith, C.M.; Gundlach, A.L.
Abstract : This cover image, by M. Haidar et al., is based on the Research Article Relaxin‐3 inputs target hippocampal interneurons and deletion of hilar relaxin‐3 receptors in "floxed‐RXFP3" mice impairs spatial memory, DOI:10.1002/hipo.22709 .